(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Adolescence is an age when the logical, physical, social, emotional and all the competencies are very high, but, unluckily, most of the teenagers are incapable of utilize their potential to supreme level due to various reasons. They confront with many problems like alcoholism, drug abuse, anti-social acts, etc. that have an adverse effect on them and others too, to a large extent. study focuses on the importance of life skills education and the benefits of imparting life skill education in our programme i.e. developing social, emotional thinking skills in students, as they are the key building base for a strong national, who can cope up with future challenges, and survive well .Present study aims to find out the life skill effect on adolescent, random sampling technique 120 (60 pre-life skill training and 60 post-life skill training)government school adolescent were taken. An exploratory design was used for the study. Life skill scale developed by Dr.Vranda (2011) is used to measure life skill impact on students. The obtained result of the study revealed there is significant difference among adolescent on life skill scale after training than before training.